The NRC Postdoctorate Fellowships, 1948-1978 - Tickner, A. (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractFollowing World War II the National Research Council established a programme of Postdoctorate Fellowships to meet the increasing need for postdoctoral training. Initially for tenure in the NRC laboratories and overseas, the fellowships were rapidly extended to Canadian universities, other federal departments and agencies and, eventually, Canadian industries. The development and achievements of the programme are reviewed from its inception in 1948 to its transfer to the new Natural Sciences and Engineering Research Council in 1978.